(untitled) (Third Sector Social Economic Review, 2020)
Party of Union and Progress takes an essential place in Turkish political life. Since both it was the first political party and won a victory over the absolute monarchy, this essential place of the Party of Union and Progress can be proved. The Party of Union and Progress was established by a group of students who were military and military medicine men. Union and Progress that worked like secret service, in the beginning, spread into the social sphere afterward and moved towards to being a political party. Much as the Committee of Union and Progress has been negatively criticized within the historical process, it left significant effects in both the late-term Ottoman and early period of Republic. In this regard, this study endeavored to scrutinize historical-sociological background, intellectual foundations, the position of political party typology and women’s policies of Union and Progress.